Posisi Manajer Untuk Wanita : Kendala dan Pandangan Islam - Rika Lidyah (Pusat Studi Gender dan Anak Universitas Islam Negeri Raden fatah palembang, 2017)
Leadership considered important in the organization because of two factors: the existence of the fact that the replacement of leaders often change the performance of an organization or agency, unit; and the research results that showed one of the internal factors that affect the success of the organization is leadership. Nowadays, it is not a strange thing when a woman occupied the highest office in an organization. Many women managers and emerging leadership and not a few who achieved success. The difference in the nature of women and men will take differences in the leadership of women and men. Men's leadership style is characterized by the ' command and control ' was originally considered to be the best. However, the stories of successful women as leader in an organization have proved that the leadership style of ' command and control ' is not the only way to reach the top of the leadership.